Effects of exposure to Di-(2-ethylhexyl) phthalate (DEHP) during lactation and puberty on sexual maturation and glycemic homeostasis in males rats. Issue 1 (February 2015) - Venturelli, Amanda Caroline; Fischer, Stefani Valeria; Nogueira de Morais, Rosana; Grassiolli, Sabrina; Martino Andrade, Anderson Joel
Summary: This study aimed to evaluate the effects of Di-(2-ethylhexyl) phthalate (DEHP) exposure during lactation or puberty on the glycemic homeostasis and the sexual maturation of male rats. Thus, in a first experiment, Wistar rats were exposed to DEHP (7.5 mg/kg/day and 75 mg/kg/day) from the 1st to the 21st day of lactation. The dams and their male offspring were evaluated regarding weight gain, food ingestion, serum concentrations of glucose and lipids, and insulin tolerance test (ITT). In addition, the male offspring was submitted to the quantification of insulin secretion in pancreatic islets isolated in vitro, concentration of fecal androgen metabolites and determination of the age of prepucial separation. In a second round of experiments, peripuberal male rats were exposed to the same DEHP doses for 30 days (22nd to 52nd day of life). These animals were evaluated regarding weight gain and food ingestion, concentration of fecal androgen metabolites, and prepucial separation along the treatment period. The ITT and analysis of serum concentrations of glucose and lipids were carried out at the end of the treatment. The male offspring presented higher vulnerability to DEHP exposure, revealing changes in the glycemic homeostasis in adulthood, characterized by the increase in fasting glycemia, decrease in insulin sensitivity and lower insulin secretion in isolated pancreatic islets. The concentrations of cholesterol and triglycerides were reduced in the offspring exposed during lactation. The animals exposed throughout the pubertal period also presented alterations in the fasting glycemia (hyperglycemia). The DEHP doses used in this study did not induce any alteration in the androgenic status of rats that were exposed either during lactation or puberty. Overall, our results suggest that DEHP exposure during lactation or puberty can induce metabolic changes at doses that do not induce classical anti-androgen alterations.